McRainey And Russick, Eds., Connecting Kids To History With Museum Exhibitions - Kaplan, Jeffrey (Teaching History: A Journal of Methods, 2010)
The key to this wonderful new text on teaching history is defined by the authors’ adherence to one basic principle- that "play and fun" are the motivating factors in all learning. Simply, if individuals love what they are doing, they will learn. With this practical advice in mind, the editors illustrate how teaching, especially with young people, can and should occur outside the classroom door. Told through a collection of highly accessible essays, the readers learn in both practical and theoretical terms how to use a museum to its optimum advantage. The authors, like others, want to demonstrate how "museums designed with kids in mind" can engage young people in learning something more than just historical people, places, and things. Divided into three essential sections- "Valuing Kids," "Connecting Kids to History," and "Creating History Exhibitions for Kids"-this is a user-friendly text for anyone who works with young people. The key, as they say, is to allow students to become immersed in hands-on activities- and what better place to start than at a museum?